Co-operative cross-platform courseware development - H. Moule; S. W. Lay; R. D. Harding (Association for Learning Technology, 1996)
Of all the TLTP projects, the UKMCC (UK Mathematics Courseware Consortium) has involved the largest number of institutions in authoring courseware. This was part of a deliberate attempt to set up an 'open courseware' system which can continue to be adapted and grow even after the end of TLTP funding. In turn, such an objective requires a cross-platform approach to courseware development. Even when considering the academic community across a single subject at just one time, there will be a variety of hardware and software that people will want to use, but a ghost of a case can be made out for attempting some sort of standardization. When change over time is considered, it is inconceivable that hardware and software platforms will remain unchanging, and one way to manage changing standards is to have a courseware structure that permits variety. This allows different parts of a collection of materials to evolve at different speeds.